Cocoa flavanol supplementation in optimizing post-exercise glycemic control in rats with normoglycemia or diabetes mellitus: findings from the ECODIA study - Bruno Pereira Melo; Joyce Camilla Cruz de Oliveira; Aline Cruz Zacarias; Letícia Maria de Souza Cordeiro; João Gabriel da Silveira Rodrigues; Mara Lívia dos Santos; Gleide Fernandes de Avelar; Romain Meeusen; Elsa Heyman; Camila Berbert Gomes; Pedro Henrique Madureira Ogando; Danusa Dias Soares (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: This study investigated the acute effects of cocoa flavanol (CF) supplementation on glucose homeostasis, aerobic performance, and lactate concentration in rats with type 1 diabetes mellitus (T1DM), type 2 diabetes mellitus (T2DM), and normoglycemia (NORM). Materials and methods: The study included 28 male Wistar rats (220-290 g). Induction of T1DM (n = 8) was achieved through intraperitoneal injection of streptozotocin, while T2DM (n = 10) was induced using an ad libitum high-fat diet combined with a fructose-rich beverage. The rats in the NORM group (n = 10) received a standard diet for 30 days. Two experiments were conducted: (1) T1DM rats performed two successive 30-minute treadmill runs below the anaerobic threshold and (2) T2DM and NORM rats underwent two incremental maximal treadmill running tests, both after CF or placebo supplementation. Blood glucose concentrations were measured from pre-exercise to 60 minutes post-exercise. Results: Glycemic reduction at 60 minutes post-exercise was significantly potentiated by CF compared with placebo supplementation in T1DM, T2DM, and normoglycemic rats (p < 0.05 for all). In T2DM rats, CF induced a glycemic response comparable to the NORM placebo-supplemented condition. These effects of CF persisted despite variations in aerobic performance or lactate concentration after incremental exercise. Conclusion: Supplementation with CF prior to physical exercise elicited a pronounced post-aerobic exercise glycemic reduction. This represents a promising strategy for mitigating the duration of hyperglycemia exposure after physical exercise.